The dilemma of career choice: a case study of Kenyan secondary school students - Kimiti, Richard Peter; Maria, Mwova Mary (Scholarly Research Journal for Interdisciplinary Studies, 2012)
The purpose of this study was to investigate the variables that influence career choice among secondary school students in Kenya. The study was guided by two objectives: to determine the influence of peer groups on students’ career choice at secondary school level and to determine the impact of career guidance and information on students’ career choice. The study adopted a survey design. Purposive and random sampling techniques were used to select the sample of the study. The sample of the study comprised of 24 teacher-counsellors and 240 form four students in twelve selected schools in Machakos and Kitui Counties, Kenya. Two data collection instruments were used for this study; teachers’ and students’ questionnaires. The data was analyzed by the use of frequencies and percentages. The results of the study revealed that only 17.50% of the student respondents stated that they were influenced by their peers when choosing their future career. Presence of career guidance programmes was evident in all the schools selected for this study. Majority of the student respondents (89.5%) indicated that the provision of career guidance and information helped them to make better decisions in choosing their career. The study recommends that peer education should be emphasized in schools since students would be equipped with the proper knowledge and information on career choice. In addition all schools should put in place effective career guidance and counselling departments. The teacher-counsellors should also be in-serviced on issues related to career choice. This will help the students to have more confidence on the career guidance services provide in schools and thus assist them to make proper decisions when selecting their careers.
Keywords: Career choice; Career guidance; Peer influence